2007
DOI: 10.1002/jsfa.2866
|View full text |Cite
|
Sign up to set email alerts
|

Wheat quality in organic and conventional farming: results of a 21 year field experiment

Abstract: Consumers have become more aware of healthy and safe food produced with low environmental impact. Organic agriculture is of particular interest in this respect, as manifested by 5.768 million hectares managed pursuant to Council Regulation (EEC) 2092/91 in Europe. However, there can be a considerable risk that the avoidance of chemical inputs in organic farming will result in poor food quality. Here the results of a study on the quality of wheat (Triticum aestivum L.) grown in a 21 year agrosystem comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
4
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 13 publications
14
137
4
2
Order By: Relevance
“…These properties also resulted in the separation of the O and LI sites on the discriminant analysis figure (Figure 1). At the same time, no difference was found either in the protein content or in the gluten content under the two management systems, similarly to the findings of Mäder et al (2007), but differences were observed in the quality traits of the gluten and in their standard deviation.…”
Section: Effect Of the Management System On Qualitysupporting
confidence: 75%
See 1 more Smart Citation
“…These properties also resulted in the separation of the O and LI sites on the discriminant analysis figure (Figure 1). At the same time, no difference was found either in the protein content or in the gluten content under the two management systems, similarly to the findings of Mäder et al (2007), but differences were observed in the quality traits of the gluten and in their standard deviation.…”
Section: Effect Of the Management System On Qualitysupporting
confidence: 75%
“…In contrast, Mäder et al (2007) found no difference either in the protein content or in the amino acid composition, mineral content and baking quality of varieties grown under organic or high-input conventional farming systems. No differences were observed for the flavour, aroma or colour attributes of conventional and organic bread, but organic bread was denser in texture with smaller air cells in the crumb (Annett et al 7 2007, Kihlberg et al 2006).…”
Section: Introductionmentioning
confidence: 56%
“…The existing research on this topic indicates that chemical crop protection does not negatively affect the quality of yields (Mäder et al, 2007;Zorb et al, 2009). The deterioration in some quality parameters is associated with the simultaneous impact of climate and soil conditions and a negative response of wheat cultivars to the chemical applied (Kieloch, Sumisławska, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported nutritional differences between organic and conventionally grown food include increases in micronutrient and vitamin content and highquality N (Worthington et al 2001;Bourn and Prescott 2002;Williams 2002;Ryan et al 2004;Annett et al 2007) whereas others have found little or no differences (Zo¨rb et al 2006;Ma¨der et al 2007). However, there are very few well-controlled studies that make valid comparisons between the nutritional qualities of organic vs. conventionally produced food (Magkos et al 2003).…”
mentioning
confidence: 98%